A ) h = -16 t² + 135 t + 76
Let : h = 0
0 = - 16 t² + 135 t + 76
B ) t 1/2 = (-b+/- √ ( b² - 4 ac ) / ( 2 a )
t 1/2 = (-135 - √(18,225 + 4,864))/ (-32) = ( - 135 - 151.95) / (- 32)=
= (-286.95) / (- 32) = 9.967 ≈ 9.0 s ( other solution is negative )
Answer:
2) 0 = -16 t² + 135 t + 76; 9 s
Step-by-step explanation:
Statement:
2-) ∠BAC = ∠EDC
<em>Reason:</em>
Angles opposite to equal sides of a triangle are equal (Alternate Interior Angles Theorem)
Statement:
3-) AC = CD
<em>Reason:</em>
CPCTC ("Corresponding Parts of Congruent Triangles are Congruent")
Statement:
4-) ∠BCA = ∠DCE
<em>Reason:</em>
Vertical Angles Theorem (states that vertical angles, angles that are opposite each other and formed by two intersecting straight lines, are congruent)
Statement:
5-) triangle ABC = triangle DEC
ASA Postulate
The ASA (Angle-Side-Angle) postulate states that if two angles and the included side of one triangle are congruent to two angles and the included side of another triangle, then the triangles are congruent. (The included side is the side between the vertices of the two angles.)
<h2>22</h2><h3>Answer: B</h3><h3 /><h2>23</h2><h3>Answer: D</h3><h3 /><h2>24</h2><h3>Answer: A</h3><h3 /><h2>25</h2><h3>Answer: C</h3>
Answer:
m∠x ≈ 32°
Step-by-step explanation:
We can see that we have to use tan∅ to solve this (opposite over adjacent)
tan(x) = 7/11
x = tan^-1 (7/11)
x = 32.4712
Answer:
f(x) = √(x+1) -2
Step-by-step explanation:
Since you're working with transformed functions, you know that replacing x with x-a in f(x) will translate the graph "a" units to the right. You also know that adding "b" units to the function value will translate the graph "b" units upward.
Here, the graph of f(x) = √x has been translated 1 unit to the left (a=-1) and 2 units down (b=-2). So, the transformed function is ...
f(x) = √(x-(-1)) + (-2)
f(x) = √(x+1) -2 . . . . . . simplify